2019
DOI: 10.1177/0300060519843686
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategy of central vein perforation accompanied by a mediastinal lesion after catheterization

Abstract: Central vein perforation associated with a mediastinal lesion is a rare complication of catheterization. A 50-year-old woman was diagnosed with chronic kidney disease and required hemodialysis treatment. The patient developed central vein injury during attempted placement of a double-channel catheter. A computed tomographic scan and venography showed that the catheter had punctured the mediastinum from the central vein. After comprehensive assessment and multidisciplinary consultation, percutaneous catheter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The outcomes of these published cases ranged from favorable to fatal. [3][4][5][6][7][8][9] Clinical outcomes or treatment plans for patients with HDC malpositioned into the mediastinum should be considered according to the position of the injured vessels. Injury of relatively large veins, such as the innominate vein or the superior vena cava, can lead to fatal outcomes, which can require emergency interventions such as ballooning or surgical repair.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcomes of these published cases ranged from favorable to fatal. [3][4][5][6][7][8][9] Clinical outcomes or treatment plans for patients with HDC malpositioned into the mediastinum should be considered according to the position of the injured vessels. Injury of relatively large veins, such as the innominate vein or the superior vena cava, can lead to fatal outcomes, which can require emergency interventions such as ballooning or surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Injury of relatively large veins, such as the innominate vein or the superior vena cava, can lead to fatal outcomes, which can require emergency interventions such as ballooning or surgical repair. 5,6,8,9 Collier et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The catheter was removed, and the right IJV was secured. Previous studies have reported favorable fatal outcomes after the malpositioning of the HDC into the mediastinum [8][9][10]. Treatment options for complications are primarily based on the position of the injured vessels, the stability of the patient, and available expertise.…”
Section: Manjunathmentioning
confidence: 99%